Tinjauan Yuridis Tentang Judi Online Di Indonesia - Nur Kholis Ahmad Sain; Tri Susilowati; Muhammad Ajid Husain (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2023)
This research is entitled "Judicial Overview of Online Gambling in Indonesia" the world as a whole has entered the world of Cyber or cyberspace, starting from that we can get all the information in the world easily through the development of technology that exists today, but along with The development of technology has had positive impacts felt by humanity. The negative thing is that there is a lot of gambling circulating on social media as a result of the development of technology. The positive impact is that people find it easier to find information and communicate more easily using social media. This research uses Normative research, namely by analyzing and analyzing secondary data in the form of secondary legal materials in order to understand the law as a set of positive regulations or norms in the legislative regulatory system. The results of this research, according to the applicable regulations, whoever misuses the opportunity to play online gambling is a criminal offense as stipulated in Article 27 of Law no. 19 of 2016 concerning amendments to law no. 11 of 2008 concerning electronic transactions reads: "every person intentionally and without right distributes, transmits, or makes accessible information or electronic documents that involve sales." Therefore, to tackle online gambling in Indonesia, three components need to be implemented, namely legal structure, legal substance and legal culture.